L’attentat contre la AMIA à Buenos Aires. Une histoire argentine ? - Sébastien Tank-Storper (Diasporas: Circulations, Migrations, Histoire, 2016)
On 18 July 1994, a bomb exploded at the headquarters of AMIA, a Jewish Community Center located in the Once neighborhood of Buenos Aires, killing 85 people and injuring 250. This attack came less than two years after the 17 March 1992 bombing of the Israeli Embassy in Buenos Aires, which killed 29 and wounded 242. Yet today 22 years later, the investigation to clarify the circumstances of the AMIA attack, Argentina’s deadliest bombing ever, has still not been completed. This article focuses on political demonstrations and memorials linked with the AMIA bombing, specifically how they raised questions about the place of Jews in Argentina’s political life. Two contradictory tendencies can be observed: a tendency to take refuge behind the ‘wall’ of the community, leading Jewish spaces to be seen as places for a separate ‘foreign’ group; and a contrary trend placing Jews in the center of Argentina’s citizens, by converging political claims for justice for the victims of the AMIA bombing with other struggles for human rights in post-dictatorial Argentinian democracy.